Financial Statement Analysis Game (FINSAGAME) / Hasni Abdullah, Nur Zahidah Bahrudin and Zahariah Sahudin - Abdullah, Hasni; Bahrudin, Nur Zahidah; Sahudin, Zahariah (Division of Research and Industry Linkages, 2017)
In fostering quality teaching, the involvement of entire institution is very important. It includes the participation from the institutional level, programme level as well as individual level. The focus of this project is to explore the individual level that encourages teachers to innovate and create adequate strategies of teaching to promote the conducive and interesting learning environment. One of the key elements that are needed by teachers in encouraging quality teaching is related to the quality of learning activity. It means that the evaluation of quality teaching is measured by the final stage of the process, enhance the learning experiences of the students. Therefore, the Financial Statement Analysis Game (FinSAGAME) is designed to help students to link with the basic theory and concept in fundamentals of finance and accounting. This game will provide a solid foundation of items in financial statements (statement of profit and loss, statement of financial position) as well as examples from real-life scenarios of business. The game allows for quick reference by students for the relevant terms and points that are extremely useful for the chapter concerned